A security system implementation using software agents. (3rd April 2006) - Shakshuki, Elhadi; Luo, Zhonghai; Gong, Jing
This paper presents multi-agent system architecture to protect hosts and users. The main objective of this system is to provide a secure environment to users at two levels. At the first level, the user is authenticated and authorised. At the second level, the messages are encrypted, decrypted, signed and verified. The system architecture is comprised of three tiers. At the front end of the system, interface agents interact with the users to fulfil their interests. At the middle tier of the system, service guard agents act as the system safeguard by authenticating and authorising users so that they can access the system and use the service resources appropriately. At the back end of the system, service provider agents offer different security services to different users. This paper provides the system and the agents' design as well as the implementations of the agents that make them capable of working together to provide a secure environment. A prototype of the system is implemented to demonstrate how the agents communicate and coordinate their activities to provide a secure environment.